2017
DOI: 10.1111/ijau.12105
|View full text |Cite
|
Sign up to set email alerts
|

Big 4 audit fee premiums for national‐ and city‐specific industry leadership in the UK: Additional evidence

Abstract: This study investigates the relationship between Big 4 auditor industry specialization and audit pricing in the UK in a period of many changes having taken place in the market for audit services. Using a large dataset between 2004 and 2011, our empirical results show a significantly higher fee premium for the Big 4 firms who are national industry leaders compared to city‐specific industry leaders, and that the fee premium for industry leadership is only earned by the city‐specific industry leaders if and when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 50 publications
(143 reference statements)
9
17
0
Order By: Relevance
“…While it is evident that a partner's industry specialization plays an important role in audit quality in the US (Nagy, 2014), Sweden (Zerni, 2012), Australia (Goodwin & Wu, 2014), and Taiwan (Chin & Chi, 2009), the extent to which partner industry expertise contributes to higher audit quality still remains an unanswered empirical question in the UK audit market. Previous studies in the UK showed that city-industry specialization was important, but not national specialization (Basioudis & Francis, 2007), and later that both national and industry level specialization was needed in order to earn an audit fee premium (Mohd Kharuddin & Basioudis, 2018). Thus, this study examines whether industry expertise at the partner level is independently associated with audit pricing.…”
Section: A C C E P T E Dmentioning
confidence: 91%
See 3 more Smart Citations
“…While it is evident that a partner's industry specialization plays an important role in audit quality in the US (Nagy, 2014), Sweden (Zerni, 2012), Australia (Goodwin & Wu, 2014), and Taiwan (Chin & Chi, 2009), the extent to which partner industry expertise contributes to higher audit quality still remains an unanswered empirical question in the UK audit market. Previous studies in the UK showed that city-industry specialization was important, but not national specialization (Basioudis & Francis, 2007), and later that both national and industry level specialization was needed in order to earn an audit fee premium (Mohd Kharuddin & Basioudis, 2018). Thus, this study examines whether industry expertise at the partner level is independently associated with audit pricing.…”
Section: A C C E P T E Dmentioning
confidence: 91%
“…specialization from the city level (Basioudis & Francis, 2007) to the national level (Mohd Kharuddin & Basioudis, 2018).…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations
“…This change exposes auditors to greater accountability and tempts legitimacy issues that may affect their reputation (Brasel et al 2016;Gimbar et al 2016;Kachelmeier et al 2014). In response, audit firms may change their norms and working patterns (Kharuddin and Basioudis 2018;Srinidhi and Gul 2007). However, such increased demand on auditors has not yet brought commensurate concern for individual practitioners and their characteristics.…”
Section: Introductionmentioning
confidence: 99%